STUDENT’S READING COMPREHENSION OF DIFFERENT GENRES IN SMP NEGERI 2 PANCURBATU - Puan Suri Mira Annisa; Bahagia Saragih (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2021)
The purposes of the study were to (1) find out the level of students reading comprehension of different genres and (2) to describe students reading comprehension of different genres of text. The subject of the research was the eight grade students in SMP Negeri 2 Pacurbatu. The research was conducted by using descriptive qualitative method. The data were collected by using reading comprehension test and interview. Then The data were analyzed by identifying the result of test first, describing the result and the last was explaining the result. Based on the result of the data analysis, it was found that the students were good at both literal and inferrential. Literal comprehension was 75.95% better than inferrential comprehension 72,68 %. Furthermore, students reading comprehension of narrative texts was the dominant genre with 75.00% which belonged to good category and followed by recount text with 72.98%, procedure text with 73.79% and the last was descriptive text with 69.75% which the only genre belonged to fair category